Evaluation of diversity, population structure and core collection of Thailand Luffa cylindrica germplasm accessions - Perez, Grimar Abdiel; Karoojee, Supasuta; Tongyoo, Pumipat; Chunwongse, Julapark; Chuenwarin, Paweena (Agriculture and Natural Resources, 2022)
Importance of the work: A Luffa cylindrica (sponge gourd) germplasm collection based in Thailand is vital for breeding programs to improve fruit quality and enhance the biotic and abiotic adaptive traits or commercial traits. Objectives: To explore the population structure and diversity in the germplasm collection. Materials & Methods: Germplasm consisting of 254 accessions was evaluated using 3,442 single nucleotide polymorphisms based on DArTSeq genotyping-by-sequencing technology. Results: The collection was divided into two (K = 2) genetic subpopulations based on STRUCTURE analysis. The genetic differentiation between these two clusters (F statistic [FST] 0.076) and variance based on the analysis of molecular variance analysis (7.6%) revealed a low differentiation between the two subpopulations. These results corresponded with principal coordinates analysis and neighbor-joining analysis in which the accessions were weakly clustered. The total collection displayed moderate diversity (expected heterozygosity = 0.310 and observed heterozygosity = 0.267) accompanied by low inbreeding (inbreeding coefficient = 0.138, and global inbreeding coefficient = 0.205). A range of simulated core collections was generated for practical field evaluation and to reduce the cost of seed maintenance in the gene bank, from which 20% of the total accessions were considered ideal. Main finding: The moderate-to-low diversity germplasm within the population will be useful for improving sponge gourd in Thailand. Increasing the diversity of sponge gourd germplasm in Thailand should be considered.